2010
DOI: 10.1002/jsfa.4189
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antioxidant and antimicrobial activities of essential oil ofAllium sphaerocephalonL. subsp.sphaerocephalon(Liliaceae) inflorescences

Abstract: The results showed that the examined species had strong antioxidant and antimicrobial properties and are in accordance with the popular use of plants belonging to the genus Allium in traditional medicine, emphasising the necessity of further detailed study of the active principles in Allium species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Antibacterial and antifungal effects of crude extracts of Allium plants have been studied extensively in food science (Najjaa et al2007 , Mau et al 2001, Lazarevic et al2011, Yin et al 1999) and medicine (Chen et al , 2011 , Seyfi. et al , 2010, Lee et al , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Antibacterial and antifungal effects of crude extracts of Allium plants have been studied extensively in food science (Najjaa et al2007 , Mau et al 2001, Lazarevic et al2011, Yin et al 1999) and medicine (Chen et al , 2011 , Seyfi. et al , 2010, Lee et al , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Vegetables of the genus Allium , such as garlic, onions, green onions, and chives, have been used as food additives in China and Egypt, and are now being studied for the prevention of infection [1012] and cancer [13, 14]. The characteristic odor of garlic and chives arises from allicin (allyl 2-propene thiosulfinate or diallyl thiosulfinate) and other oil-soluble sulfur components, such as diallyl disulfide (DADS), diallyl trisulfide (DATS), and diallyl sulfide (DAS) [1518].…”
Section: Introductionmentioning
confidence: 99%
“…The antifungal properties of sulfur compounds have been known for many centuries. The use of plant extracts is in general an alternative form of therapy for mycosis and candidiasis [1]. Literature data showed that there are directly proportional relationships between the type and concentration of the sulfur from A. ursinum and antimicrobial action of these plants [2].…”
Section: Introductionmentioning
confidence: 99%